Mental Readiness of Physical Education Students for Odd Semester Lectures in 2023 - Eko Nopiyanto, Yahya; Raibowo, Septian; Prabowo, Andika; Sari Kardi, Ipa; Ibrahim (Indonesian Journal of Physical Education and Sport Science, 2023)
Studi purpose. Mental preparation affects a person's performance in achieving and realizing their hopes, especially in the fields of education and sports. This study aims to reveal the level of mental readiness of physical education students in attending lectures in the odd semester of 2023. This research seeks to reveal the level of mental readiness of physical education students to attend lectures in the odd semester of 2023. Materials and methods. This research is quantitative. The population in the study was 250 students. The research sample was chosen randomly so that there were 112 students. Research data was collected using an instrument in the form of a questionnaire. Analysis of research data using simple statistics with standard deviation formulas and ideal mean values so that five categories are formed. Results. The results of the analysis illustrate that 34 students have very high mental readiness, 62 students have high mental readiness, 12 students have moderate mental readiness, 3 students have low mental readiness, and 1 student has very low mental readiness. Conclusions. It was concluded that students have high mental readiness to attend lectures in the odd semester of 2023.